STRATEGIES FOR TEACHING MIXED-ABILITY ADULT ENGLISH CLASSES - Sattarova D.I,; Murtazayeva. D.U, (TADQIQOTLAR, 2026)
Abstract Article  explores  effective  strategies  for  teaching  mixed-ability  adult  English classes, addressing the diverse needs and learning styles of adult learners. It emphasizes the importance of creating an inclusive and supportive classroom environment that fosters engagement and promotes language acquisition. The article discusses various instructional techniques, such as differentiated instruction, collaborative learning, and the use  of technology, to  accommodate  varying  proficiency  levels. Additionally, it highlights  the  significance  of  assessing  learners'  needs  and  providing  personalized feedback  to  enhance  their  learning  experience.  By  implementing  these  strategies, educators can effectively meet the challenges posed by mixed-ability classrooms and facilitate meaningful language learning for all students.